Web marketing all-in-one for dummies - Arnold, John, 1972-; Lurie, Ian; Marsten, Elizabeth; Dickinson, Marty; Becker, Michael, 1969- (--For dummies., 2009)
If your business, organization, or association needs to reach people who use computers for shopping, browsing the Internet, or interacting with others, you need Web marketing. And if you need Web marketing, you need this book. Here are some reasons why. Successful Web marketing requires you to place and maintain your messages on multiple Internet mediums because your prospects and customers use those same Internet mediums to help them look for products and services. You don't have to be a technical expert to reap the rewards of Web marketing, but you do need to understand how people behave when they fire up their Internet browser, e-mail program, or mobile phone; that way, your marketing messages are always top-of-mind when customers are ready to make a purchase. This book is really eight minibooks, each covering a topic related to Web marketing. Each minibook covers a topic in its entirety, so each is a concise -- yet comprehensive -- path to learn about the Web marketing topics you need to know about.